Integrated frameworks of unsupervised, supervised and reinforcement learning for solving air traffic flow management problem - Huang, Cheng; Xu, Yan (IEEE, 2021)
This paper studies the demand-capacity balancing (DCB) problem in air traffic flow management (ATFM) with collaborative multi-agent reinforcement learning (MARL). To attempt the proper ground delay for resolving airspace hotspots, a multi-agent asynchronous advantage actor-critic (MAA3C) framework is firstly constructed with the long short-term memory network (LSTM) for the observations, in which the number of agents varies across training steps. The unsupervised learning and supervised learning are then introduced for better collaboration and learning among the agents. Experimental results demonstrate the scalability and generalization of the proposed frameworks, by means of applying the trained models to resolve different simulated and real-world DCB scenarios, with various flights number, sectors number and capacity settings.
Keywords: DCB; Multi-agent; Reinforcement Learning; Unsupervised Learning; Supervised Learning